Interventional radiological approaches to non-variceal gastrointestinal bleeding - Se Hwan Kwon; Seung Yeon Noh; Joo Hyeong Oh (Society of Gastrointestinal Intervention, 2023)
Although many cases of gastrointestinal bleeding (GIB) respond to medical and endoscopic management, GIB is often a serious clinical dilemma. Massive GIB can lead to significant morbidity and mortality unless appropriate treatment is not performed. Diagnostic and therapeutic approaches to GIB depend on its location, severity, and etiology. Interventional radiological management (intra-arterial infusion of vasopressin and transcatheter arterial embolization) is a safe and effective minimally invasive alternative to surgery for the management of GIB that is refractory to endoscopic treatment. The present review discusses the essential role of interventional radiology in the management of GIB.